PERAN ORDER INVESTOR DALAM MENJELASKAN TERBENTUKNYA POLA VOLUME PERDAGANGAN DI BURSA EFEK INDONESIA (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia) - Silvia Qotrun Nada; Afifudin Afifudin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTIONThe purpose of this study is to examine 1) the role of the order informedinvestor in explaining trading volume 2) the role of the order informed investor inexplaining trading volume.Data in this study using secondary data on first semester during Februaryto April period 2018, with the number of the sample 45 companies. Analysis toexamine the correlation of the variables using multiple linear regression.The result shows the selling of informed investor, the buying of informedinvestor, the selling of uninformed investor, the buying of uninformed investorpositively influenced to trading volume. Moreover, the selling of informed investorand the buying of informed investor positively influence to trading volume.Nevertheless, the selling of uninformed investor and the buying of uninformedinvestor negatively influenced to trading volume.Keywords: order, informed investor, uninformed investor, trading volume, IDX